Analysis of mechanical properties and distribution of deformation during the shear of polymer-fiber composites containing flame retardants - Oliwa, Rafał; Bulanda, Katarzyna; Oleksy, Mariusz; Budzik, Grzegorz; Krauze, Sławomir (Polimery, 2020)
The work examined the effect of flame retardant addition to the epoxy resin powder matrix on the mechanical properties of composites reinforced with biaxal glass fabric. Two flame retardant systems were used to modify the epoxy resin: (1) melamine polyphosphate (MPP) and aluminum diethyl phosphinate (AlDPi); (2) ammonium polyphosphate (APP) and dipentaerythritol (DPE). The flame retardant content was 25 wt %. In addition, individual compositions also contained 15 wt % of zinc borate (ZB). Tensile, bending and shear tests for the obtained composites were performed. Furthermore, using the digital image correlation method, an analysis of local strains on the sample surface during shear test was carried out. The obtained results indicate, that the amount and type of flame retardant affects the mechanical properties of the composites. Among the tested systems, the best results were obtained for a composite containing 18 wt % ammonium polyphosphate and 7 wt % dipentaerythritol. Compared to the reference sample, among others, the shear stress and shear modulus increased by 25.0 and 39.7%, respectively. In turn, a clear deterioration of the tested parameters was observed in the case of a composite with a matrix containing 15 wt % of AlDPi, 10 wt % of MPP and 15 wt % of ZB, because, compared to unmodified composite, the flexural, tensile and shear stress were reduced by 50.9, 53.5 and 34.8%, respectively.